Biopolymer-based Edible Film for Food Packaging Application : Review - Matovanni, Maudy Pratiwi Novia; Jannah, Erisa Nur; Utami, Aliyya Nisa Budi; Maritza, Damara Ramadhani; Pertiwi, Beta Cahaya (UPN Veteran Jatim, 2025)
Edible films serve as an effective barrier to prevent mass transfer between the product and its environment. This innovation facilitates the development of environmentally sustainable food packaging alternatives that promote the efficient use of natural resources. A variety of biopolymers are utilized in the formulation of edible films, primarily polysaccharides, proteins, and composite materials. Polysaccharides can be further categorized according to their origin, including plant, animal, marine, microbial, and industrial waste sources. Proteins are generally classified into plant- and animal-based categories. Composite films, which combine multiple biopolymer types, offer enhanced structural properties. The application of biopolymer-based edible films presents a promising strategy for mitigating commercial plastic waste accumulation. Nevertheless, the incorporation of additives—such as plasticizers, antioxidants, and antimicrobial agents—is essential to enhance film properties and ensure compliance with quality standards for food packaging application